Memberi Dampingan Untuk Menumbuhkan Rasa Kasih Diantara Anak-anak Panti Asuhan Niscahaya Indonesia Dengan Bermain dan Saling Berbagi Cerita - Lulu Dewi Sari Simbolon (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The fieldwork practice carried out at the Niscahaya Indonesia orphanage aims to get closer to the children who are in the orphanage by providing assistance in learning letters, doing assignments, providing material on English and also playing. The method used in the practice of this field activity is the group work method, and the group work method used is the group work recreation group. The PKL team planned simple activities to help the children catch up on learning letters more quickly and be united and love each other. The results of this field work practice were appreciated by the children, the children were very grateful for the presence of the PKL team. They feel happy even in a relatively short period of time.